The impact of education on unemployment incidence and re-employment success: Evidence from the US labour market - W. Craig Riddell; Xueda Song (Institute for the Study of Labor (IZA), 2011)
This study investigates the causal effects of education on individuals' transitions between employment and unemployment, with particular focus on the extent to which education improves re-employment outcomes among unemployed workers. Given that positive correlations between education and labour force transitions are likely to be confounded by the endogeneity of education, we make use of data on compulsory schooling laws and child labour laws as well as conscription risk in the Vietnam War period to create instrumental variables to identify the causal relationships. Results indicate that education significantly increases re-employment rates of the unemployed. Particularly large impacts are found in the neighborhoods of 12 and 16 years of schooling. Evidence on the impact of formal schooling on unemployment incidence is mixed.
urn:nbn:de:101:1-201104133943
Keywords: I20; J64; 330; education; labour market transitions; unemployment; causal effects; compulsory schooling laws; child labour laws; Vietnam War draft; Arbeitslosigkeit; Berufliche Integration; Bildungsniveau; Schulbesuch; Jugendarbeitsschutz; Schätzung; USA; Wehrdienst; Krieg; Vietnam